Implementasi Strategi Peer Assisted Learning (PAL) untuk Meningkatkan Literasi Anatomi Mahasiswa Calon Guru Biologi - Sariwulan Diana (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2016)
Research on Peer Assisted Learning (PAL) strategy implementation in Plant Anatomy Course, which aims to improve anatomic literacy of prospective student’s biology teacher, has been done.  This study used an experimental method, with a quasi experimental pretest posttest control group design. The draft includes a group of students who were given a pre-test (tests performed before PAL treatment) which is then followed by observing the PAL treatment process and posttest. The other students group (control) was given the pretest and posttest only. The research instruments include a questionnaire to recruit tutor, a set of pretest and posttest questions about anatomic literacy, tutorial about anatomic literacy, and questionnaires about student response to the PAL program. The results showed that the student’s anatomic literacy in Plant Anatomy course increased with moderate category (N-gain 0,38) in the experimental class and lower category (N-gain of 0,14) in the control class. There was significant difference between the student’s anatomic literacy that used the PAL strategy and control class with t value 3,729 greater than t table 5,278 at α 0,001. Thus the PAL strategy implementation can be used to improve student’s anatomic literacy. All students respond positively to the PAL strategy.